Pengaruh Abu Janjang Kosong Kelapa Sawit dengan Kompos Eceng Gondok terhadap Perubahan Sifat Kimia Tanah Lahan Pasang Surut - Syifa Syifa; Meldia Septiana; Ismed Fachruzi (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2024)
Marshes that are affected either directly or indirectly by the ebb and flow of seawater are known as tidal wetlands. The lack of soil nutrients like low pH, N, P, and K, as well as the high solubility of Al and Fe, which can poison plants, is the problem with tidal wetlands. The goal of the study was. to find out how the application of oil palm empty fruit bunch (EFB) ash and water hyacinth compost changed the pH, organic C, N, P, and K levels of the soil in tidal wetlands. The randomized complete design (CRD) method was used in this pot experiment, with two factors: 1) four applications of oil palm EFB ash, and 2) four applications of water hyacinth compost. Oil palm EFB ash had doses of 0 ton.ha-1, 1 ton.ha-1, 1.5 ton.ha-1, and 2 ton.ha-1, while water hyacinth compost had doses of 0 ton.ha-1, 2 ton.ha-1, 3 ton.ha-1, and 4 ton.ha-1, respectively. 32 experimental units were created when 16 treatment combinations were replicated twice. After four weeks of incubation, the soil was submerged in water to a height of 5 cm. The application of oil palm EFB ash and compost made from water hyacinths had significant effects on pH, N-NO3ˉ, available P, and K, but not organic C or N-NH4+. The findings suggest that the application of water hyacinth compost and oil palm EFB ash can raise the pH, organic C, and levels of N, P, K in the soil.